Ocular complications in live-related renal transplant recipients: a single-centre study - Lanewala, Fatema Ali; Akhtar Jamal Khan (Journal of the Pakistan Medical Association, 2023)
Renal transplantation is considered to be the treatment of choice for patients with end-stage kidney failure. While transplantation has a high success rate, there are a number of associated challenges which include those related to the primary disease, transplant procedure as well as medications that are necessary to take after transplantation. Steroids, for instance, have been reported to lead to ocular complications in patients who have undergone renal transplantation in other parts of the world. This retrospective case series reports the pattern of ocular complications among patients who underwent renal transplant since the inception of ophthalmology clinic at a dialysis and transplant centre in Karachi, Pakistan. The case series corroborates the findings of other similar studies from around the world, with cataract being the most common occurrence in this cohort. A unique finding in Pakistani setup includes the high prevalence of night blindness, —Continue